2015
DOI: 10.1080/15384047.2015.1030556
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor cell isolation during resection of colorectal cancer lung and liver metastases: a prospective trial with different detection techniques

Abstract: Blood sampling during CRC metastasis resection is an opportunity to increase CTC capture efficiency. CTC isolation with the FMSA yields more CTCs than the CellSearch® system. Future studies should focus on characterization of single CTCs to identify targets for molecular therapy and immune escape mechanisms of cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 62 publications
2
72
0
Order By: Relevance
“…In comparison, CellSearch detected CTCs in 22% (4/18) of samples. The higher rate of CTC detection using the FMSA compared to CellSearch was corroborated by another recent clinical study (Kaifi et al, 2015).…”
Section: Two-dimensional Microfiltration Systemssupporting
confidence: 68%
See 1 more Smart Citation
“…In comparison, CellSearch detected CTCs in 22% (4/18) of samples. The higher rate of CTC detection using the FMSA compared to CellSearch was corroborated by another recent clinical study (Kaifi et al, 2015).…”
Section: Two-dimensional Microfiltration Systemssupporting
confidence: 68%
“…Constructed from parylene-C, can process WB, captures viable cells, clusters observed Kaifi et al, 2015) 3D FaCTChecker Constructed from parylene-C, captures viable cells between membrane layers Parsortix Viable cells released by reversing flow Resettable Cell Trap Pneumatically-controlled microvalves (Qin et al, 2015) Cluster Chip Triangular pillars designed for CTC clusters (Sarioglu et al, 2015) Biophysical e Inertial Focusing Cells are passively separated by size through the application of inertial forces in microfluidic devices that affect positioning within the flow channel.…”
Section: D Track-etched Isetmentioning
confidence: 99%
“…24,25 To further address this we initiated a clinical trial on intraoperative CTC isolation during CRC lung and liver metastasectomy, comparing the CellSearch Ò system with a sizebased CTC isolation technique (ClinicalTrials.gov Identifier: NCT01722903) that demonstrated higher CTC capture efficiency intraoperatively with an innovative filter. 31 Several studies have demonstrated the clinical significance of CTC numbers as a prognostic marker when enumerated by the CellSearch Ò system in metastatic tumors of breast, colon and prostate. 12,26,27 However, CellSearch Ò is limited by the selection of EpCAMC CTCs only.…”
Section: Discussionmentioning
confidence: 99%
“…Response to treatment in one lung cancer patient was monitored using the NanoVelcro technology in addition to whole genome amplification and Sanger sequencing to detect relevant mutations in EGFR at time points before and after treatment with Gefitinib [16]. Consequences of metastasectomy were evaluated through CTC enumeration over multiple time points with the FMSA device in metastatic colorectal cancer patients [40]. Microfluidic technologies have also been used to illuminate biological subtleties of these cells in transit.…”
Section: Applications Of Ctc Isolation Technologiesmentioning
confidence: 99%